#TITLE_ALTERNATIVE# - JONATHAN (NIM : 10506035); Pembimbing : I Nyoman Marsih, PhD, ELIEZER
Cobalt catalysts with zeolite supports are one of the most potent catalysts to be developed for carbon monoxide hydrogenation reaction (Fischer-Tropsch reaction). This study compares cobalt catalysts, supported by either hydrothermal synthetic zeolite or hydrothermally purified natural zeolite. The synthetic zeolite is synthesized by hydrothermal reaction from sodium sylicate and aluminium sulphate, while the natural zeolite is purified by soaking in concentrated alkaline solution to form a slurry, which then separated from larger impurities by decantation and conditioned in high pressure hydrothermal reactor at 200 oC for 48 hours. The comparison of crude natural zeolite, alkaline conditioned natural zeolite, and hydrothermally purified natural zeolite XRD diffractograms gives the last method as the purest of the three. Both the purified natural zeolite and synthetic zeolite then impregnated by cobalt nitrate solution to give Co/zeolite catalyst. The reactivity of catalysts can be estimated from their surface areas. The XRD diffractograms shown that synthetic zeolite has a rather good purity, the SEM photos shown the porous structures of zeolite particles. The surface areas of cobalt catalysts with synthetic zeolite support are 0.9577 m2/g, larger than the surface area of the support that was 0.0600 m2/g.